Values – standards – goods - Hausner, Jerzy (Journal of Public Governance, 2018)
Values can be instrumentalized individually, but they are social in origin. They derive from the fact that individuals enter into social relationships and need the community in order to ensure that such relationships are consolidated and respected. Values exist provided that they are produced, and the process of producing them is social in nature. It is people who generate values, values are not given to them. Value creation is a social process in which certain values generate others and simultaneously multiply (reinforce) the initial, existential ones that underlie the entire process.